Sediment distribution in turbulent flow - Dac, Nguyen Tat; Son, Pham (Vietnam Journal of Mechanics, 1980)
Using the classical diffusive equation with variable coefficient of diffusion the authors solve a problem concerning with sediment distribution in turbulent flow having construction. The sediment concentration distribution is pointed out in the paper.